2019
DOI: 10.3390/admsci9020040
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Conditional Value at Risk in the Tehran Stock Exchange Based on the Extreme Value Theory Using GARCH Models

Abstract: This paper attempted to calculate the market risk in the Tehran Stock Exchange by estimating the Conditional Value at Risk. Since the Conditional Value at Risk is a tail-related measure, Extreme Value Theory has been utilized to estimate the risk more accurately. Generalized Autoregressive Conditional Heteroscedasticity (GARCH) models were used to model the volatility-clustering feature, and to estimate the parameters of the model, the Maximum Likelihood method was applied. The results of the study showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…where u N represents the number of exceedances over the threshold u and n is the sample. By substituting Equations (18) and (20) into Equation 19…”
Section: Modelling Tails Using Extreme Value Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…where u N represents the number of exceedances over the threshold u and n is the sample. By substituting Equations (18) and (20) into Equation 19…”
Section: Modelling Tails Using Extreme Value Theorymentioning
confidence: 99%
“…In recent studies in finance VaR is be estimated more accurately using the conditional-EVT approach especially in modelling the distribution of extreme events and estimating extreme tail risks than the conventional models. Moreover, in some other studies, the conditional Value-at-Risk has been used as the risk measure, and researchers have shown that theoretically and empirically, using [18] showed that the GARCH-EVT model outperforms the simple GARCH model with Student's t and normal distributions for residuals.…”
Section: Introductionmentioning
confidence: 99%
“…The EVD is fruitful in forecasting when there is a heavier right tail on the underlying prices in market and to describe extremely unlikely events [27]. The EVD with real parameters µ as the location parameter and σ as the scale parameter presents a statistical continuous distribution given over the set of real numbers.…”
Section: Var Based On the Evdmentioning
confidence: 99%
“…Shrestha et al [14] and Valipour et al [15] analyzed risk allocation. Hamed et al [16] and Dixit and Tiwari [17] estimated conditional value at risk. Hatefi and Tamosaitiene [18] presented the model for evaluating construction projects by considering interrelationships among risk factors.…”
Section: Introductionmentioning
confidence: 99%